Estudos das práticas de preservação de documentos em papel do Poder Judiciário do Estado do Pará / Arquivo Regional de Belém - TELES, Aluizio dos Santos (2023)
Analysis about the methods of preservation of documents carried out by the Court of Justice of the State of Pará - Regional Archive of Belém (ARB), identifying strengths and possible weaknesses. It was made a bibliographical research about conservation and preservation of documents and the history, characteristics and agents of paper deterioration, with an exploratory analysis and case study focused on the Belém Regional Archive, based on a visit to the site and an interview with the archive employee. It was identified that the Belém Regional Archive performs satisfactorily the practices of preservation and conservation of documents. However, a greater financial contribution is suggested to enhance these initiatives, combined with the insertion of an archivist in the team of employees in the organism.